PLANNING OF FLEXIBLE PAVEMENT THICKNESS FOR NEW RUNWAY IN SUPADIO INTERNATIONAL AIRPORT WITH FEDERAL AVIATION ADMINISTRATION METHOD - Dian, Ansela Brigita; Akhmadali, Akhmadali; Kadarini, S. Nurlaily; Widodo, Slamet; Mukti, Elsa Tri (Jurnal Teknik Sipil, 2022)
The runway is one component in the airport system, its performance greatly affectsall airport operational activities. Anticipating the increase in services from thecapacity of the number of passengers, it is necessary to build a new runway. In thisstudy, analyze the forecast of the number of movements with the trend analysismethod and the percent forecast method from PT. Angkasa Pura II, field subgradeCBR, new runway capacity and planning year, and new runway pavement using theFederal Aviation Administration (FAA) method and FAARFIELD 1.42 software.Based on the analysis results, the field subgrade CBR was 0.38% 3%, then it wasstabilized using selected soil (CBR 20.523%) with a thickness of 60 cm. The forecastresults with both methods show that the trend analysis method is used because thetime is earlier than other methods, namely in 2027 with the existing runway capacityat Supadio International Airport of 54 operations/hour with a maximum capacity of51 operations/hour. The results of the runway flexible pavement thickness using theFAA method manually obtained a total pavement thickness of 42" (107 cm), whichconsists of 4"(10 cm) Surface Course, 12"(31 cm) Base Course, and 26"(66 cm)Subbase Course, while the FAARFIELD 1.42 software has a total pavementthickness of 30.43"(77 cm), which consists of 4"(10 cm) Surface Course, 5" (13 cm)Base Course, and 21.43"(54 cm) Subbase Courses.